Doppler tracking for position determination 2 - Chan, Yong Hong. (2012)
Doppler Tracking allows the distance between a satellite transmitting from space and a radio receiver on the ground to be measured by analysing how the frequency received from the satellite changes as it approaches, passes overhead, and moves away from the receiver. The position vectors of the receiver can then be calculated since the satellite position, determined by ephemeris data tagged with time produced by the downlink radio signal transmitted from the satellite to the receiver, and Doppler measurements involving computing Doppler count from the analysed frequency are known.